Development of Android-based Learning Media for Economics Learning - Sri Wahyuni; Suarman Suarman; Rr Sri Kartikowati (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to develop android-based learning media to help economics lessons, especially in national income materials for Class XI students of the Department of Social Sciences at the senior high school level. The research method used was research and development (RD), with the ADDIE model. The media was then implemented in class XI students, with a total of 20 students. The research sample was selected purposively with consideration of the material in the media and the ease of research. Media demands, student profiles, and the learning environment were observed and interviewed for study. The media was planned and developed using Articulate Storyline 3, validated by 3 media and 2 material specialists (Expert Judgement), and analysed qualitatively. Student and instructor responses to questions on media practicality and usefulness were quantified. The entire ADDIE circuit was evaluated at each stage. The results of the analize stage prove that students and teachers need support media for material related to economic statistics. The design and development of media was carried out by researchers by providing several advantages including simple and interesting, interactive media that can be used in offline and online modes. Its excellence gained the recognition of eligibility from validators. Student response at the limited trial and implementation stage showed the media had a practicality level which is high and very useful. In fact, economics teachers at both schools gave a perfect assessment (maximum score) for all indicators of the teacher response questionnaire statement. It can be concluded that the media was needed by students and teachers based on economic statistics. The media was designed and developed with advantages based on needs analysis. The media was valid and should be implemented.